The political constitution : the case against judicial supremacy - Weiner, Greg (University Press of Kansas, 2019)
Who should decide what is constitutional? The Supreme Court, of course, both liberal and conservative voices say--but in a bracing critique of the "judicial engagement" that is ascendant on the legal right, Greg Weiner makes a cogent case to the contrary. His book, The Political Constitution, is an eloquent political argument for the restraint of judicial authority and the return of the proper portion of constitutional authority to the people and their elected representatives. What Weiner calls for, in short, is a reconstitution of the political commons upon which a republic stands. At the root of the word "republic" is what Romans called the res publica, or the public thing. And it is precisely this--the sense of a political community engaging in decisions about common things as a coherent whole--that Weiner fears is lost when all constitutional authority is ceded to the judiciary. His book calls instead for a form of republican constitutionalism that rests on an understanding that arguments about constitutional meaning are, ultimately, political arguments. What this requires is an enlargement of the res publica, the space allocated to political conversation and a shared pursuit of common things. Tracing the political and judicial history through which this critical political space has been impoverished, The Political Constitution seeks to recover the sense of political community on which the health of the republic, and the true working meaning of the Constitution, depend
Keywords: United States. -- Congress -- Powers and duties.; États-Unis. -- Congress -- Pouvoirs et fonctions.; United States. -- Congress; Political questions and judicial power -- United States.; Judicial power -- United States.; Judicial review -- United States.; Delegation of powers -- United States.; Politique et pouvoir judiciaire -- États-Unis.; Pouvoir judiciaire -- États-Unis.; Contrôle juridictionnel des lois -- États-Unis.; United States.; HISTORY.; Constitutions.; POLITICAL SCIENCE.; American Government.; Legislative power; Judicial review; Judicial power; Delegation of powers; Political questions and judicial power; United States; Electronic books.